Geistliche Liederdichter zwischen Liturgie und Volkssprache Übertragungen, Bearbeitungen, Neuschöpfungen in Mittelalter und Früher Neuzeit - Kraß, Andreas; Standke, Matthias (Liturgie und Volkssprache, 2020)
Composers of spiritual songs in the Middle Ages and Early Modern Period, including the Monk of Salzburg, Oswald von Wolkenstein, Heinrich Laufenberg, and Sebastian Brant, engaged productively with the tradition of Latin hymns and sequences. This volume collects thirteen studies on songs by these and other composers who stood at the intersection between liturgy and the vernacular.